Rap1 Guanosine Triphosphate Hydrolase (GTPase) Regulates Shear Stress-Mediated Adhesion of Mesenchymal Stromal Cells - Melanie Giesen; Erika Fleck; Jürgen Scheele; Tanja Nicole Hartmann; Reinhard Henschler (Biology)
Intravenously transplanted mesenchymal stromal cells (MSCs) have been shown to interact with endothelial cells and to migrate to tissues. However, intracellular signals regulating MSC migration are still incompletely understood. Here, we analyzed the role of Rap1 GTPase in the migration of human bone marrow-derived MSCs in vitro and in short-term homing in mice in vivo. MSCs expressed both Rap1A and Rap1B mRNAs, which were downregulated after treatment with siRNA against Rap1A and/or B. In a flow chamber model with pre-established human umbilical vein endothelial cells (HUVECs), Rap1A/B downregulated MSCs interacted for longer distances before arrest, indicating adhesion defects. CXCL12-induced adhesion of MSCs on immobilized Vascular Cell Adhesion Molecule (VCAM)-1 was also decreased after the downregulation of Rap1A, Rap1B, or both, as was CXCL12-induced transwell migration. In a competitive murine short-term homing model with i.v. co-injection of Rap1A+B siRNA-treated and control MSCs that were labeled with PKH 26 and PKH 67 fluorescent dyes, the Rap1A+B siRNA-treated MSCs were detected at increased frequencies in blood, liver, and spleen compared to control MSCs. Thus, Rap1 GTPase modulates the adhesion and migration of MSCs in vitro and may increase the bio-availability of i.v.-transplanted MSCs in tissues in a murine model.